Systematic Review Comparison of Endotracheal Intubation Success Rate Using McGrath® Mac Videolaryngoscope with Direct Laryngoscope (Macintosh): A Manikin Studies - Dicha Niswansyah Auliyah; Lilik Herawati; Prananda Surya Airlangga (Faculty of Medicine-Universitas Airlangga, 2021)
Introduction: McGrath® MAC videolaryngoscope is a single-handed device designed to facilitate intubation in patients both in patients with normal airway conditions (without any complications) or airway conditions with complications such as cervical spine and/or anatomic abnormalities. Objective: This study aims to compare McGrath® MAC videolaryngoscope and direct laryngoscope using Macintosh blades as learning material or study simulators for medical personnel (including anesthesiologist and paramedics) and novice operator (medical students). Method: this study is a systematic review using the PRISMA method which was carried out systematically. Data was collected through Pubmed, direct science, EBSCOHost, and Proquest using the keywords ‘airway management ', ‘laryngoscopy', and 'manikin'. Journal included based on published publication time between 2008 and 2020, a study using SimMan Laerdal Airway manikin, a journal discussing intubation using McGrath® MAC videolaryngoscope and direct laryngoscope with Macintosh blades here, where it is normal airway (without complications) and difficult airway. Results: 1556 journals were collected through 4 journal search sites and then carried out a screening process for the publication year approved in 2008 to 2020. Four studies use adult manikin SimMan Laerdal Airway including 247 participants were included in this systematic review. Conclusion: Based on journals that have been reviewed, McGrath® MAC videolaryngoscope provides better and superior results compared to Macintosh in terms of the success rate and visualization of glottis. Also, the intubation time using McGrath® MAC videolaryngoscope is shorten compared to Macintosh both on the normal airway (without complication) and difficult airway. The participants (medical personnel and novice operators) in all studies that reviewed prefer to use McGrath® Mac videolaryngoscope instead of using direct laryngoscope with Macintosh blade for Endotracheal Intubation mainly used for learning or study simulators.